Investigating the Relationship between Self-Directed Learning and E-Citizenship knowledge and its comparison between Students of University of Mazandaran and Babol University of Medical Sciences - fatemeh marhemati; reza mir arab razi; mostafa azizi (Babol University of Medical Sciences, 2020)
Background and Objective: Creating and developing self-directed learning skills has become one of the goals of education in recent decades, and today's students need to learn and acquire comprehensive information in this regard, or better to say, learn information and communication technology skills, to Be able to use electronic services. The purpose of this study was to investigate the relationship between electronic citizenship knowledge and self-directed learning of students of University of Mazandaran and Babol University of medical sciences.   Methods: This study is descriptive-analytical in terms of research method. The statistical population of the study consisted of two categories: Students of Mazandaran University in summer 1397, 11960 (in 13 colleges of this university) and Students of Babol University of Medical Sciences in summer 1397, 3410 (in 8 faculties the sampling method was a multi-stage comparative class. Using Krejcy-Morgan table, the sample size was 372 for Mazandaran University and 345 for Babol University of Medical Sciences. Chow test and Z-Fisher test were used to analyze the data. Standard questionnaires of electronic citizenship knowledge of Manson Choi et al. (2017) and self-directed learning of Darlene and Peder (2010) and SPSS statistical analysis software were used. Chow test and Z - Fisher test was used to analyze the data. Findings: The students were selected from Mazandaran University and Babol University of Medical Sciences in different ages, genders and faculties. But no significant difference was observed between students of two universities in different classes (value F = 1.22). Conclusion: The existence of a significant positive relationship between self-directed learning and e-citizenship knowledge shows the need to combine these two areas and provide a greater role for citizenship knowledge in students' self-directed learning.